Radiolytic evaluation of acetohydroxamic acid (AHA) under biphasic (HNO3:n-dodecane and TBP/DEHBA/DEHiBA) used nuclear fuel reprocessing conditions. (June 2023) - Umpleby, Rachel E.; Conrad, Jacy K.; Wilbanks, Joseph R.; Schaller, Kastli D.; Horne, Gregory P.
Abstract: Acetohydroxamic acid (AHA) has been proposed as a substitute for hydrazine-stabilized reductants for the selective separation of plutonium and neptunium from co-extracted uranium during the reprocessing of used nuclear fuel. However, limited information exists for the chemical behavior of AHA in ionizing radiation fields, especially under representative biphasic reprocessing solvent system conditions. Here we present a systematic gamma irradiation study on the radiolytic integrity of AHA in aqueous nitric acid solutions (0.2 M HNO3 ) in contact with an organic phase, comprising current (tri-butyl phosphate) and next generation ( N, N -di-(2-ethylhexyl)butyramide and N, N -di-(2-ethylhexyl)isobutyramide) reprocessing ligands dissolved in n -dodecane diluent. Biphasic AHA irradiations exhibited negligible effect of the organic phase on the rate of AHA radiolysis—affording an average pseudo dose constant of d' = (−58.66 ± 6.10) × 10 −4 kGy −1 —and subsequent formation of the predominant degradation products (hydroxylamine and acetic acid), relative to complementary single-phase systems. The radiolysis of AHA was found to have negligible impact on ligand degradation rates: G (TBP) = −0.038 ± 0.002 μmol J −1, G (DEHBA) = −0.117 ± 0.004 μmol J −1, and G (DEH i BA) = −0.102 ± 0.003 μmol J −1 . These observations demonstrate that the radiolytic transients and steady-state degradation products generated in either phase have limited capacity for migrating across the aqueous-organic interface to undergo subsequent chemistry within the investigated dose range (≤110 kGy). These findings support the substitution of AHA into advanced reprocessing flowsheets. Highlights: The gamma radiation stability of AHA was evaluated in biphasic systems. AHA degraded exponentially with absorbed dose in both single and biphasic systems. Organic phase ligands (TBP, DEHBA, and DEH i BA) degraded linearly with absorbed dose. Biphasic irradiations had negligible impact on single phase degradation rates.